Exploring the Strengths and Weaknesses of Ruangguru as Online Learning Platform to Support Students’ Learning Activity - Titin Arifa Maulida; Saiful Akmal (Proceedings of AICS - Social Sciences, 2021)
The existence of Ruangguru as one of the online learning platforms in Indonesia has helped students to learn at home individually. Ruangguru smartphone application allows virtual learning to become more organized in adjusting the curriculum. Ruangguru provides exclusive features to facilitate online learning, which makes this application widely used by students. However, many believe that Ruangguru still cannot replace face-to-face learning activities. Therefore, this research aimed to explore the strengths and weaknesses of this platform based on the students’ experience. The participants were five senior high school students batch 2021 from two courses in Banda Aceh who have experienced learning conventional/offline courses and online learning by Ruangguru. This research uses a qualitative approach with interview and observation as the data collection techniques. Based on the research findings, Ruangguru allows learning in an environment without time and place restriction. It is proven capable enough of changing the barriers caused by poverty, location, and other factors. However, Ruangguru could not replace conventional learning, especially in the context of social interaction. The main reason is that Ruangguru only focuses on the students’ learning achievements. However, some other significant aspects are overlooked such as low feedback, lack of peer interaction, and unscheduled learning.Keywords: Ruangguru Application; Online Learning Platform; Conventional Learning